2020
DOI: 10.1097/md.0000000000023679
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy and immunoregulatory effect of Qiangji Jianli Capsule for patients with myasthenia gravis

Abstract: Introduction: Myasthenia gravis (MG) is an autoimmune disease in which antibodies directly target components of the neuromuscular junction, causing neuromuscular conduction damage that leads to muscle weakness. The current pharmaceutical treatment for MG is still not ideal to address the problems of disease progression, high recurrence rate, and drug side effects. Clinical observations suggest that traditional Chinese medicine (TCM) can strengthen immunity and improve symptoms of MG patients, dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Spleen-kidney deficiency syndrome was reported to be the major syndrome of MG patients in China. [16,34]. In TCM theory, the kidney governs the bone and acts as the root of primordial Qi to dominate growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Spleen-kidney deficiency syndrome was reported to be the major syndrome of MG patients in China. [16,34]. In TCM theory, the kidney governs the bone and acts as the root of primordial Qi to dominate growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the heterogeneous components of Chinese herbs, the onset time and half-time of Chinese herbs are hard to confirm [ 24 ]. According to previous clinical observation and preliminary trial [ 11 ], we decided to set the intervention period or control period for 4 weeks and the wash-out interval for 1 week. Each cycle comprises a 4-week intervention period with MBYD combining conventional western medicine and a 4-week control period with placebo with the same western medicine in random order.…”
Section: Methodsmentioning
confidence: 99%
“…A study found that using TCM combined with western medicine might improve the total effect and reduce the risk of MG relapse [ 9 ]. According to the TCM characteristic theory of “spleen governing muscle,” MG is generally diagnosed as “spleen qi deficiency syndrome” and thereby, strengthening the spleen and replenishing qi is a common therapeutic strategy of MG in TCM, which has played a positive role in clinical practice of MG [ 10 , 11 ]. Buzhong Yiqi decoction (BYD), a classical qi -supplementing formula in TCM, is the most frequently used prescription to treat MG. A study showed that BYD modulated the balance of Treg and Th17 cells in patients with MG and downregulated the serum AChR antibody level [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the heterogeneous components of Chinese herbs, the onset time and half-time of Chinese herbs are hard to con rm (24). According to previous clinical observation and preliminary trial (11), we decided to set the intervention period or control period for 4 weeks and the wash-out interval for 1 week. Each cycle comprises a 4-week intervention period with MBYD combining conventional western medicine and a 4-week control period with placebo with the same western medicine in random order.…”
Section: Methods Trial Designmentioning
confidence: 99%
“…A study found that using TCM combined with western medicine might improve the total effect and reduce the risk of MG relapse (9) . According to the TCM characteristic theory of "spleen governing muscle", MG is generally diagnosed as "spleen qi de ciency syndrome" and thereby, strengthening spleen and replenishing qi is a common therapeutic strategy of MG in TCM, which has played a positive role in clinical practice of MG. (10,11) Buzhong Yiqi Decoction (BYD), a classical qi-supplementing formula in TCM, is the most frequently used prescription to treat MG. A study showed that BYD modulated the balance of Treg and Th17 cells in patients with MG, downregulated the serum AChR antibody level (12). Modi ed BYD (MBYD) is based on BYD and adds other Chinese herbs to treat MG patients' speci c or concurrent symptoms synergistically.…”
Section: Introductionmentioning
confidence: 99%